The oppressive house: The inner eye in Fernando de Szyszlo’s surrealist short film Esta pared no es medianera - Delgado Chumpitazi, Mónica Grisell (2023)
In 1952, Peruvian painter Fernando de Szyszlo made his only short film, Esta pared no es medianera. Along with other Latin American short films that emerged in the mid-twentieth century, this film expresses an interest in recovering some of the expressive forms of emblematic films from the 1920s that belonged to the surrealist movement, whether from the use of images in a dreamlike key or from some of the precepts of the thematic universe around the power of the unconscious. This film also reflects that almost three decades after the publication of the Manifesto of Surrealism (1924), this literary and artistic movement remained vital in Peru, not only through gatherings, debates, publications of poems, but also from the creative process and topics of this film. From the study of the motif of the house as an interior space of oppression, this article establishes connections between the theoretical concept of the interior model (or inner eye) and the proposal of interpellation to that idea developed in Szyszlo’s film. In this sense, this text seeks to demonstrate that through the figure of the house a poetics of oppression is constructed in this short film, in opposition to the exterior spaces that embody the liberation of the unconscious free of guilt, and therefore, to the inner eye.